Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/0264-9381/24/15/002
|View full text |Cite
|
Sign up to set email alerts
|

Cosmologies with a general non-canonical scalar field

Abstract: We generally investigate the scalar field model with the lagrangian L = F (X) − V (φ), which we call it General Non-Canonical Scalar Field Model. We find that it is a special square potential(with a negative minimum) that drives the linear field solution(φ = φ 0 t) while in K-essence model(with the lagrangianthe potential should be taken as an inverse square form. Hence their cosmological evolution are totally different. We further find that this linear field solutions are highly degenerate, and their cosmolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 87 publications
(58 reference statements)
0
45
0
Order By: Relevance
“…Unnikrishnan et al [57] have showed that for such models, the slow-roll conditions can be more easily satisfied compared to the canonical case. The non-canonical scalar field models are also found to be able to generate inflation in the early epoch [45,[47][48][49][50][51][52][53][54][55][56][57][58][59]. These attractive features of a noncanonical scalar field motivated us to study the features of this model in the context of dark energy.…”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unnikrishnan et al [57] have showed that for such models, the slow-roll conditions can be more easily satisfied compared to the canonical case. The non-canonical scalar field models are also found to be able to generate inflation in the early epoch [45,[47][48][49][50][51][52][53][54][55][56][57][58][59]. These attractive features of a noncanonical scalar field motivated us to study the features of this model in the context of dark energy.…”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
“…In case of the phantom field, the sign of its kinetic term "X" is opposite compared to the action for a canonical scalar field. The Lagrangian density for a general non-canonical scalar field is given by [59] …”
Section: Field Equations and Their Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for these models, we can use Lagrangians with a non-canonical kinetic term, namely a term which is an arbitrary function of the square of the time derivative of the scalar field, in the homogeneous and isotropic background. These models are known as "k-essence models" [3,4,5,6,7,8] (see also [9,10,11,12,13,14]) and have been inspired by earlier studies of k-inflation [15] [16] (a complete list of dark energy models can be found in the review [17]). …”
Section: Introductionmentioning
confidence: 99%
“…However, for most of the dark energy models the analysis is carried out for canonical scalar fields. But there is another class of scalar field models, viz, non-canonical scalar field models which have also been considered as a candidate for dark energy (for details see [11][12][13] and the references there in). This class of models has also been found to be a very good candidate for dark energy and could provide solution to a number of cosmological problems.…”
Section: Introductionmentioning
confidence: 99%